A Cross-National Analysis of the Wages of Part-Time Workers: Evidence from the US, UK, Canada, and Australia - Janet C. Gornick; Jerry A. Jacobs (Luxembourg Income Study (LIS), 1994)
Hourly wage differentials between part-time and full-time workers, using comparable microdata from LIS for the US, UK, Canada, and Australia are examined. Institutions and policies that contribute to different outcomes for part-time workers in these countries, and implications of these policies are also discussed in the context of policy reform.
Keywords: 330; Teilzeitarbeit; Lohnstruktur; Australien; Großbritannien; Kanada; USA